Isolation and Characterization of Propoxur-Degrading Bacteria, Brucella pseudintermedia LED 6 from a Pineapple Plantation in Lampung - Taufiq Hidayat; Rahayu Widyastuti; Gunawan Djajakirana; Sarjiya Antonius; Tirta Kumala Dewi (Institut Pertanian Bogor, 2025)
Propoxur is a non-systemic carbamate insecticide that is widely used in Indonesia to control insect pests. However, its persistence and toxicity pose environmental concerns. Bioremediation with bacteria is a viable method for mitigating the detrimental effects of propoxur residues. The goal of this work was to isolate and characterize bacterial strains that can degrade propoxur. Isolation by enrichment culture procedures, utilizing propoxur as the sole carbon source. The isolates' morphological and physiological features were examined, and their degradation potential was determined. Six bacterial samples were isolated from a pineapple plantation in Lampung, Indonesia, and one strain, known as LED 6, showed great potential for propoxur breakdown. Molecular identification with 16S rRNA gene sequencing identified the isolate as Brucella pseudintermedia. Growth characterisation revealed that the isolate performed best at 28 °C and pH 7. After 72 hours of incubation with 500 ppm propoxur, LED 6 had deteriorated around 26% of the starting concentration. Keywords: bioremediation, Brucella pseudintermedia, pineapple, propoxur